Anxiety, enjoyment, and boredom in language learning amongst junior secondary students in rural China: How do they contribute to L2 achievement?. Issue 1 (8th March 2023) - Li, Chengchen; Wei, Li
Abstract: Building on the control-value theory, the present study examined the independent and joint predictive effects of three emotions—enjoyment, anxiety, and boredom—on L2 achievement over time. The participants of the study were a group of junior secondary English learners in rural China, a population that has hitherto never featured in L2 learning research. Questionnaire data and achievement data were collected at four different time points (Time 1–Time 4: T1–T4) from a large sample of 954 learners. Structural equation modeling results show that: (a) the three emotions at T1 predicted English achievement at T2 (one week after T1) and T3 (five weeks after T1) independently, while only enjoyment predicted achievement at T4 (nine weeks after T1); (b) when combined, enjoyment was the strongest and most enduring predictor across T2–T4, followed by anxiety predicting achievement at T2–T3 negatively, while boredom completely lost its predictive power across T2–T4.